PERBEDAAN FAKTOR PREDISPOSING, ENABLING DAN REINFORCING ANTARA IBU YANG MEMBERIKAN ASI EKSKLUSIF DAN NON ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS BOYOLALI 1 KABUPATEN BOYOLALI - Anik Widyastuti; Priyadi Nugraha Prabamurti; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Exclusive breastfeeding is breastfed given to babies since birth for about six months without adding or replacing with other foods or beverages. According to the Indonesian Health Profile report in 2014, the total achievement of exclusive breastfeeding in Indonesia have not met the 2014’ target of strategic plan that is 80%, it only can reach amount 52,3%. Total achievement of exclusive breastfeeding in local clinic 1 Boyolali amount 29,8%.The purpose of this research is to analyze the characteristics differences of predisposing, enabling and reinforcing between the mother who give non exclusive breastfeeding and exclusive breastfeeding in Boyolali local clinic 1 Boyolali regency. This research is a quantitative research with cross-sectional approach. The population of this research consists of 60 respondents. Sample taken use total sampling technique. The instrument used in this research is the questionnaire. Data are analyzed using univariate and bivariate statistical using T sample independent statistics test and Mann Whitney test as the alternative test (significance level 0.05).There are 2 groups of respondents in this research. One group consists of 30 mothers who give exclusive breastfeeding and another group consists of 30 mothers who do not give exclusive breastfeeding. The results of this research indicate that most respondents in the age 26-35 years (80.0%) are exclusively breastfeeding mothers while (86.0%) mothers who are not exclusive breastfeeding, the most recent education exclusively breastfed mothers are Diploma (63.3%) while non exclusive breastfeeding mothers are high school (60.0%), the occupation of exclusive breastfeeding mothers is dominated by self-employed (60.0%) while non exclusive breastfeeding mothers are civil servants (66.7 %), Both groups of mothers share a partial history of multipara. There are differences variables on exclusive breastfeeding behavior were on maternal knowledge of breastfeeding (p = 0.009), maternal attitude about breastfeeding (p = 0.048), husband support (p=0,000), family support (p=0.016) and peer support (p=0.002). Variables that do not differ in exclusive breastfeeding behavior are characteristic of respondent including age (0,492), education (1,000), occupation (1,000) and parity (1,000). Furthermore, the variable access to health services (0.125) and information access about breastfeeding (0.254). So, counseling and socialization of exclusive breastfeeding to mothers, husbands and families are needed.